Detectable serum flagellin and lipopolysaccharide and upregulated anti-flagellin and lipopolysaccharide immunoglobulins in human short bowel syndrome - Ziegler, Thomas R; Luo, Menghua; Estivariz, Concepcion F; Moore, Daniel A., III; Sitaraman, Shanthi V; Hao, Li; Bazargan, Niloofar; Klapproth, Jan-Michael; Tian, Junqiang; Galloway, John R; Leader, Lorraine M; Jones, Dean P; et al. (American journal of physiology. Regulatory, integrative and comparative physiology, 2008)
Departments of 1 Medicine, 2 Pathology and Laboratory Medicine, and 3 Surgery and 4 Center for Clinical and Molecular Nutrition, Emory University School of Medicine, Atlanta, Georgia Submitted 9 September 2007 ; accepted in final form 12 November 2007 Gut barrier dysfunction may occur in short bowel syndrome (SBS). We hypothesized that systemic exposure to flagellin and lipopolysaccharide (LPS) in SBS might regulate specific immune responses. We analyzed serial serum samples obtained from parenteral nutrition (PN)-dependent patients with SBS versus non-SBS control serum. Serum from 23 adult SBS patients was obtained at baseline and 4, 8, 12, 16, 20, and 24 wk in a trial of modified diet with or without growth hormone. Control serum was obtained from 48 healthy adults and 37 adults requiring PN during critical illness. Serum flagellin was detected by an ELISA recognizing an array of gram-negative flagellins, and LPS was detected by limulus assay. Serum flagellin- and LPS-specific immunoglobulin levels (IgM, IgA, and IgG) were determined by ELISA. Serum flagellin and LPS were undetectable in control subjects. In contrast, serum flagellin, LPS, or both were detected in 14 SBS patients (61%) during one or more time points [flagellin alone, 5/23 (22%); LPS alone, 6/23 (26%); or flagellin + LPS, 3/23 (13%)]. Flagellin-specific serum IgM, IgA, and IgG levels were markedly increased in SBS patients compared with both control populations and remained elevated during the 6-mo study period. LPS-specific IgA was significantly higher in SBS patients compared with healthy controls; LPS-specific IgM, IgA, and IgG levels each decreased over time in association with PN weaning. We conclude that adults with PN-dependent SBS are systemically exposed to flagellin and LPS, presumably from the gut lumen. This likely regulates innate and adaptive immune responses to these specific bacterial products. parenteral nutrition; intestinal barrier function Address for reprint requests and other correspondence: T. R. Ziegler, Suite GG-23, General Clinical Research Center, Emory Univ. Hospital, 1364 Clifton Road, Atlanta, GA 30322 (e-mail: tzieg01atemory.edu )